EVALUATION AND DIAGNOSIS OF DERMATOPHYTES IN MEDIA CONTAINING RICE EXTRACTS - M.Emami; F. Parsai Nasab; M. Gerami Shoar (Tehran University of Medical Sciences, 2000)
Dermatophytes are usually characterized on Sabouraud's dextrose agar (S) by their colonial morphology and microscopic sporulation. In this study, we have prepared new media by using rice extracts for the characterization of the following dermatophytes, T.rubrum, T. violaceum, T. verrucosurn, T.schoenleinii, M.canis, M.gypseum and E.Floccosum. The results of this study showed that, dermatophyte; grow well on these media in comparison with S medium. In addition, the size of colonies was much higher than that of S medium and the colony pigmentation of T.rubrum was appeared after 8 d, and colonial morphology of T.mentagrophytes was quite distinct. In rice extracts media, the optimal macro and micro conidia production were obtained. Therefore, using the rice extract to prepare selective media for growing dermatophytes presented more advantages.